Kereta Api dan Tradisi Mudik Lebaran di Bandung Tahun 1980-2014 - Herdianti, Syarifani; Permana, Agus; Tarpin, Tarpin (Historia Madania: Jurnal Ilmu Sejarah, 2018)
The history of railways in Indonesia is part of the life journey of the Indonesian people. Since its emergence in the latter part of the second half of the 19th century until now, railroad is a vital and important means of transportation, both for the benefit of the government and the community. Railroad transportation facilities are a favorite for residents to go home on the first day of Eid. In recent years, homecoming has become an interesting social-religious phenomenon to discuss. The method used in this study is a historical research method which consists of: Heuristics (collection of sources), Criticism (analyzing the accuracy and credibility of sources), interpretation of data, Historiography (historical writing). The history of railways in Indonesia began when the first using of the railway line in Semarang-Vorstenlanden (Solo-Yogyakarta) in the village of Kamijen by the Governor-General of the Dutch East Indies, Mr. L.A.J Baron Sloet Van De Beele on June 17, 1864. The construction was carried out by the private company Nederlansch Indische Spoorweg Maatschappij (NISM) using a width of 1435 mm. During the Dutch administration in addition to Staats Spoorwegen (SS) as a state company, there were 11 private railway companies in Java and one in Sumatra. The success of PT KAI in revolutionizing the train ticket service had a very wide impact, including serving Lebaran trip.